Assessing health governance across countries: a scoping review protocol on indices and assessment tools applied globally. Issue 7 (15th July 2022) - Huang, Aidan; Lin, Yuling; Zhang, Liyuan; Dong, Jingwen; He, Qiwei; Tang, Kun
Abstract : Introduction: Most global health indices or assessment tools focus on health outcomes rather than governance, and they have been developed primarily from the perspective of high-income countries. To benchmark global health governance for equity and solidarity, it becomes necessary to reflect on the current state of indices or assessment tools evaluating health governance across countries. This scoping review aims to review the existing multicountry indices and assessment tools applied globally with measurable indicators assessing health governance; summarise their differences and commonalities; identify the lessons learnt through analysis of their advantages and gaps; and evaluate the feasibility and necessity to establish a new index or consensus framework for assessing global health governance. Methods and analysis: This scoping review protocol follows Arksey and O'Malley's methodological framework, the Joanna Briggs Institute guidelines and the Preferred Reporting Items for Systematic Reviews and Meta-analyses methodology for scoping reviews. Key information sources will be bibliographic databases (PubMed, Embase and Web of Science Core Collection), grey literature and citation tracking. The time frame will be from 1 January 2000 to 31 December 2021. Only indices or assessment tools that are globally applicable and provide measurable indicators of health governance will be eligible. A qualitative content analysis will follow the proposed data extraction form to explicate and compare each eligible index or assessment tool. An analysis based on a proposed preliminary evaluation framework will identify the advantages and gaps and summarise the lessons learnt. This scoping review will also discuss the feasibility and necessity of developing a new global health governance index or consensus framework to inform future research and practices. Ethics and dissemination: This scoping review does not require ethics approval. Dissemination will include a peer-review article, policy briefs and conference presentations. This protocol has been registered in the Open Science Framework (osf.io/y93mj).